Straight Line Features Detection and Mosaic of Wind Power Blades Image - MA Baoyan; TANG Lei; ZHAO Jing; HE Yongjun (Journal of Harbin University of Science and Technology)
It is necessary to periodically inspect the blade surface of the wind turbines operation. The widely used manual inspection method brings a heavy workload, high cost and low detection rate, so it is urgent to need anautomatic inspection system.Image mosaic of wind power blades is a key part of the intelligent inspection system, which directly determines the system performance. Current splicing methods cannot extract enough feature points when facing a strip object with a single structure and color such as wind power blade, causing failure in splicing success. A splicing method based on line features is proposed to solve this problem. This method first detects straight lines in the images of the wind power blade, then selects the deduplication as the feature for image registration, and finally splices the blade image according to translation rotation matrix.Experimental results show that the proposed method shows strong robustness and stability in complex situations such as single structure, small coincidence degree and diverse backgroundstability.